Electromyographic analysis of shoulder function during the volleyball serve and spike - Rokito, A. S.; Jobe, F. W.; Pink, M. M.; Perry, J.; Brault, J. (Journal of Shoulder and Elbow Surgery, 1998)
The purpose of this study was to describe the electromyographic (EMG) pattern and relative intensities of 8 shoulder muscles during the volleyball serve and spike in 15 professional or collegiate-level athletes. The EMG analysis was synchronized with high-speed cinematography to discern phases of the spike and serve. During the spike, the anterior deltoid and supraspinatus functioned together to elevate and place the humerus throughout all phases. During cocking the infraspinatus and teres minor acted together to rotate the humerus externally. In acceleration, however, these muscles behaved independently; activity of the teres minor remained high, whereas the activity of the infraspinatus declined. The anterior wall muscles functioned to decelerate the humerus during cocking and acted as internal rotators during acceleration. Muscle activities recorded for the serve followed similar patterns as those seen for the spike, but with lower amplitudes. These data illustrate the complex sequence of shoulder muscle activity necessary to play competitive volleyball.